2006
DOI: 10.1080/14786430600724470
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen doping and multiplicity of stacking faults in SiC

Abstract: This paper reports on the strong enhancement of stacking fault (SF) formation in 4H-SiC by heavy nitrogen doping. The paper consists of two separate observations. The first part reports on localized but severe deformation bands observed in certain regions of 4H-SiC wafers that had undergone high temperature processing during device fabrication. Using a combination of dynamic secondary ion mass spectroscopy (SIMS) and conventional, weak-beam (WB) and high-resolution (HR) transmission electron microscopy (TEM), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 30 publications
0
11
0
1
Order By: Relevance
“…Also, CL images taken form highly doped epilayer do not show any sign of double stacking faults. Probably this doping range is too low to give rise to stacking fault formation [31].…”
Section: Structural Defectsmentioning
confidence: 99%
“…Also, CL images taken form highly doped epilayer do not show any sign of double stacking faults. Probably this doping range is too low to give rise to stacking fault formation [31].…”
Section: Structural Defectsmentioning
confidence: 99%
“…High-temperature heat treatment can provide the partials with the energy necessary to overcome this barrier. Calculations by Kuhr et al 5 and observations by Pirouz et al 6 showed that a faulted crystal containing these double Shockley faults is more stable than the perfect 4H-SiC crystal at temperatures greater than 1000°C, provided a threshold doping level of around 2 9 10 19 cm À3 is exceeded. The fact that we observe such stacking fault formation in more highly doped regions suggests that the doping level in those regions exceeds this threshold value.…”
Section: Formation Mechanismmentioning
confidence: 99%
“…In another study by Kuhr et al, 5 the existence of DSSFs was revealed in highly nitrogen-doped 4H-SiC samples following annealing at 1150°C in an Ar environment. Pirouz et al 6 reported the generation of DSSFs from scratches in highly n-doped 4H-SiC which were subjected to either a high-temperature annealing or a combination of an annealing plus applied stress. Kuhr et al 5 proposed an electronic mechanism for the DSSF formation and expansion.…”
Section: Introductionmentioning
confidence: 99%
“…Great advances were reported in growing a single crystalline polytype by controlled sublimation and chemical vapor deposition [1][2][3]. Polytypic transformation in SiC was investigated by many authors [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%